Scientific meaning and scope of Social Sciences - Castro Aguirre, Constancio (Huarte de San Juan. Geografía e Historia, 2021)
The scientific status for Social Sciences is under question. The main supporter of questioning seems to be a well known science historiographer Professor Sanchez Ron. Our answer is in two steps. We show in the first the Social Sciences´ beginning through the last century at the specific US scenery, thus the Harvard University along the 1930 decade. There was the starting point for the search of the empirical knowledge builded by the human behavior observations facing the social environment. The National Academy of Sciences come in this way heading its 1986 report Behavioral and Social Sciences Fifty Years of Discovery. In the second step we show the mathematical support for Behavioral Sciences without any dependence from the Physics. We had a pleasure following R. Duncan Luce’s trayectory who was granted receiving the National Medal of Science in 2003 for his contribution to Behavioral Sciences.